A model framework to retrieve thermodynamic and kinetic properties of organic aerosol from composition-resolved thermal desorption measurements - S. Schobesberger; S. Schobesberger; E. L. D'Ambro; E. L. D'Ambro; F. D. Lopez-Hilfiker; F. D. Lopez-Hilfiker; C. Mohr; C. Mohr; J. A. Thornton (Atmospheric Chemistry and Physics, 2018)
Chemical ionization mass spectrometer (CIMS) techniques have been developed that allow for quantitative and composition-resolved measurements of organic compounds as they desorb from secondary organic aerosol (SOA) particles, in particular during their heat-induced evaporation. One such technique employs the Filter Inlet for Gases and AEROsol (FIGAERO). Here, we present a newly developed model framework with the main aim of reproducing FIGAERO-CIMS thermograms: signal vs. ramped desorption temperature. The model simulates the desorption of organic compounds during controlled heating of filter-sampled SOA particles, plus the subsequent transport of these compounds through the FIGAERO manifold into an iodide-CIMS. Desorption is described by a modified Hertz–Knudsen equation and controlled chiefly by the temperature-dependent saturation concentration C*, mass accommodation (evaporation) coefficient, and particle surface area. Subsequent transport is governed by interactions with filter and manifold surfaces. Reversible accretion reactions (oligomer formation and decomposition) and thermal decomposition are formally described following the Arrhenius relation. We use calibration experiments to tune instrument-specific parameters and then apply the model to a test case: measurements of SOA generated from dark ozonolysis of α-pinene. We then discuss the ability of the model to describe thermograms from simple calibration experiments and from complex SOA, and the associated implications for the chemical and physical properties of the SOA. For major individual compositions observed in our SOA test case (#C = 8 to 10), the thermogram peaks can typically be described by assigning C*25 °C values in the range 0.05 to 5 µg m−3, leaving the larger, high-temperature fractions (>50 %) of the thermograms to be described by thermal decomposition, with dissociation rates on the order of  ∼ 1 h−1 at 25 °C. We conclude with specific experimental designs to better constrain instrumental model parameters and to aid in resolving remaining ambiguities in the interpretation of more complex SOA thermogram behaviors. The model allows retrieval of quantitative volatility and mass transport information from FIGAERO thermograms, and for examining the effects of various environmental or chemical conditions on such properties.